Let This Life Speak : the Legacy of Henry Joel Cadbury - Bacon, Margaret Hope (University of Pennsylvania Press, 2016)
Henry Joel Cadbury made his mark on twentieth-century culture as a biblical scholar and teacher of world renown, a Quaker leader, and a peace and civil rights activist.